Development of android game-based learning media "Dhamma quest" on Buddhist symbols at the Dhamma suci Buddhist sunday school - Beri Beri; Dedi Kundana; Taridi Taridi (International Journal of Science and Applied Science: Conference Series, 2025)
Rapid technological development has brought many significant changes to everyday life, changing people's mindsets and paradigms in seeking information. Nowadays, people no longer rely solely on newspapers and radio but also use other sources of information, one of which is the internet. In implementing learning, it is important to provide supporting teaching materials and resources so that educational goals can be achieved. If learning is only carried out conventionally, students tend to experience boredom and lack of active involvement. This study aims to develop an Android-based learning media in the form of the Dhamma Quest game as a tool to help Buddhist Sunday School students understand Buddhist symbols, as well as to analyze students' responses to its use in increasing their interest and understanding. In addition, this study also assesses the feasibility of the media through expert and specialist validation, as well as determining the influence of the Dhamma Quest learning media on students' interest or motivation to learn. This study also focuses on the development of learning media in the form of the "Dhamma Quest" game on Buddhist symbols at the Dhamma Suci Buddhist temple Sunday school. This study uses a level 3 research and development (R&D) method. The steps used include researching and developing the product. The research subject is the Dhamma Suci Buddhist temple Sunday school. Data collection techniques include observation, product validation observation sheets, and the one-group pretest-posttest method, while the analysis technique uses a paired samples test.The overall assessment results were given by subject matter and media experts, with an average score of 4.56 and a percentage score of 96% in the very feasible category. The limited test results showed that the posttest mean score (81.9) was higher than the pretest score (42.5). With this achievement, the Dhamma Quest media was considered effective in improving students' understanding and feasible for use as learning media for Buddhist symbols.